Impact of Anti-Corruption Education Program on Students’ Attitudes and Behavior - Ahmed Al-Sabah; Sarah Al-Jabri; Sarah Al-Sabih (International Journal of Educational Narratives, 2025)
Background. This study examines the impact of an anti-corruption education program on students’ attitudes and behavior. As corruption remains a significant challenge in many societies, fostering ethical behavior and instilling a strong anti-corruption mindset in future generations is critical. Educational interventions focused on anti-corruption are seen as a means to influence young people’s values and behaviors in the long term. Purpose. The purpose of this research is to assess how such an educational program affects students’ awareness of corruption, their attitudes toward ethical decision-making, and their personal conduct. Method. A quasi-experimental design was employed, involving pre- and post-test surveys administered to 250 high school students who participated in an anti-corruption education program. Results. The results revealed a significant improvement in students’ understanding of corruption and their commitment to anti-corruption behaviors. Students reported greater awareness of the consequences of corruption and showed stronger intentions to act ethically in personal and professional settings. Conclusion. The study concludes that anti-corruption education programs can play an important role in shaping positive attitudes and behaviors toward corruption prevention. These findings suggest that integrating anti-corruption education into school curricula can help promote integrity and reduce future involvement in corrupt practices.